2020
DOI: 10.1002/jts.22615
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Adapted Cognitive Behavioral Therapy Plus Problem Management (CA‐CBT+) With Afghan Refugees: A Randomized Controlled Pilot Study

Abstract: Culturally adapted cognitive behavioral therapy (CA-CBT) is a well-evaluated, transdiagnostic group intervention for refugees that uses psychoeducation, meditation, and stretching exercises. In the current study, we added problem-solving training to CA-CBT and evaluated this treatment (i.e., CA-CBT+) in a randomized controlled pilot trial with a sample of Farsi-speaking refugees. Participants (N = 24) were male refugees diagnosed with DSM-5 PTSD, major depressive disorder, and anxiety disorders who were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 64 publications
0
42
0
Order By: Relevance
“…Training for therapist/provider/facilitator: Thirty-two studies (36%) reported adaptations that involved the specific provision of training for whomever was providing the intervention. Examples include where training was provided to professionals (e.g., Kananian, Soltani, Hinton, & Stangier, 2020 ; Miranda, Azocar, Organista, Dwyer, & Areane, 2003 ) or to lay/community members (e.g., Bonilla-Escobar et al, 2018 ; Leiler, Wasteson, Holmberg, & Bjärtå, 2020 ) for the purpose of providing better care for the target population group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Training for therapist/provider/facilitator: Thirty-two studies (36%) reported adaptations that involved the specific provision of training for whomever was providing the intervention. Examples include where training was provided to professionals (e.g., Kananian, Soltani, Hinton, & Stangier, 2020 ; Miranda, Azocar, Organista, Dwyer, & Areane, 2003 ) or to lay/community members (e.g., Bonilla-Escobar et al, 2018 ; Leiler, Wasteson, Holmberg, & Bjärtå, 2020 ) for the purpose of providing better care for the target population group.…”
Section: Resultsmentioning
confidence: 99%
“… Grote et al, 2009 ; Lovell et al, 2014 ) including use of metaphors, or where intentional emphasis was placed on the cultural norms, practices or expectations of the target population (e.g., Gonyea, Lopez, & Velasquez, 2016 ; Knaevelsrud, Brand, Lange, Ruwaard, & Wagner, 2015 ). Explicit cultural adaptations also involved those where the authors reported that the theoretical stance of the intervention was culturally informed including use of existing theoretical models or adaptations frameworks (e.g., Bedoya et al, 2014 ; de Graaff et al, 2020 ; Hinton et al, 2005 ; Kananian et al, 2020 ; Koch, Ehring, & Liedl, 2020 ; Pan, Huey, & Hernandez, 2011 ). Explicitly reported cultural adaptations were considered in the typology with regard to both their inclusion in the common factors model and as a specific type of adaptation (explored in the analyses later).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of jigar-e-khun 3 , she likely knows that her liver is not actually bloody, as this is metaphorical, but it points to her grief feeling somehow physically manifest, including physical agitation and aggression. This somatization would be corroborated through articles on chronic pain in displaced and survivor of torture or targeted violence (TTV) populations (Kananian et al, 2020;Kaur, 2020;Rohlof et al, 2014;Rometsch-Ogioun El Sount et al, 2019;Sarajlić Vuković et al, 2014), especially since the physical consequences of TTV can serve as everpresent reminders of the humiliations endured. More importantly, regardless of how her anguish is expressed, she may identify this grief as problematic due to decreased functioning in important life domains or in her ability to fulfill reasonable responsibilities.…”
Section: Synthesis Of Clinical Perspectives and Proposalsmentioning
confidence: 95%
“…The most common group works with refugee and immigrant adults include education and psychoeducational groups, support groups, and trauma-informed groups (Sakamoto & Couto, 2017). Empirically tested effective group interventions include eye movement desensitization and reprocessing therapy (Lehnung et al, 2017; Yurtsever et al, 2018), group cognitive behavioral therapy (Hinton et al, 2012; Kananian et al, 2020; Shaw et al, 2019), trauma-focused group therapy (Drožđek & Bolwerk, 2010), and group art therapy (Dieterich-Hartwell & Koch, 2017). A meta-analysis found that both individual and group interventions on PTSD, depression, and anxiety among immigrant and refugee populations were efficacious with no significant difference between the modalities (Turrini et al, 2019).…”
mentioning
confidence: 99%